Multi-Column Semi-Submersible Floating Body Hydrodynamic Performance Analysis - Wei Wang; Jingyi Hu; Cheng Zhao; Yonghe Xie; Xiwu Gong; Dingliang Jiang (Energies)
Due to the limited availability of land resources, offshore wind turbines have become a crucial technology for the development of deep-water renewable energy. The multi-floating body platform, characterized by its shallow draft and main body located near the sea surface, is prone to significant motion in marine environments. The proper chamfering of the heave plate can effectively enhance its resistance during wave action, thereby improving the stability of the floating platform. The optimal chamfer angle is 35°. Considering the complexity of the floating body’s motion response, this study focuses on the damping characteristics of the heave plate with 35° chamfered perforations. Using the NREL 5 MW three-column semi-submersible floating wind turbine platform as the research model, the hydrodynamic characteristics of the floating body with a perforated heave plate are systematically studied through theoretical analysis, numerical simulation, and physical tests. The amplitude of vertical force under various working conditions is measured. Through theoretical analysis, the additional mass coefficient and additional damping coefficient for different working conditions and models are determined. The study confirms that the heave plate with 35° chamfered perforations significantly reduces heave in the multi-floating body.